Tradition Mēkare-Kare In Ritual Usaba Sambah In The Village Of Customary Tenganan Pegringsingan (Study of Hindu Theology) - I Nyoman Subamia (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2018)
Tradition is something that is done for generations (of ancestors) are still on the run in the community. In general, the tradition usually involves about religious elements such as religious ceremonies, as well as other religious rituals. Just as there is in the public rituals of Bali Aga village of Tenganan Indigenous Pegringsingan. Where Tenganan village is one of the traditional village which has one fairly unique tradition known as mēkare-kare, where mēkare-kare is war conducted in honor of the god Indra. The study was conducted in a qualitative, so the data analysis conducted qualitative descriptive and interpretative. With the data collection method is Reassurance, interviews and literature study. The results showed that: (1) The procession tradition mēkare-kare is one of the most important religious ceremonies and rituals are required in Usaba Sambah in the traditional village of Tenganan Pegringsingan, include (a) the procession tradition mēkare-kare, among others sangkep, gēguron, mēkare-kare mabuang pindo, mēkare-kare advanced, megibung jaja, mabuang pindo and panyineb lawang; (b) means upakara / offerings mekaré tradition-kare; (c) the place, time implementation mēkare-kare tradition; (d) equipment during mēkare-kare tradition; (e) the master of ceremonies; (f) prayer in mēkare-kare; and (g) the parties concerned. (2) Function mēkare-kare tradition in ritual usaba sambah is (a) religious functions; (b) an educational function; (c) social function; (d) the survival function of indigenous traditions; (e) the function of the show; and (f) the function to train agility. (3) The meaning of tradition mēkare-kare in usaba sambah rituals are (a) the meaning sradha bhakti; (b) the meaning of togetherness; (c) the historical significance; (d) the sociological meaning; and (e) inheritance value.